Effectiveness of Mnemonic Method on Students’ Language Information Retention - Ocampo, Darrel; Belleca, Faith Chi Dy; Caampued, Kristine; Caballas, Ryan; Guiruela, Justine Marie (Universitas Terbuka, 2025)
This study aimed to investigate how mnemonic methods, specifically acronyms and acrostic, impact language information retention among second year BSED-ENGLISH students at a state university in Camarines Sur. The research questions focused on the effects of acronyms and acrostics on retention, the effectiveness of mnemonics in improving retention, and differences in post-test results between comparison and experimental groups while considering pre-test scores. The participants are the 37 respondents from BSED-English 2A and 33 respondents from BSED-English 2B taking the Technical Writing course. A quasi-experimental design used test questionnaires as the primary tool. Statistical methods like frequency count, percentage, mean, and ANCOVA analyzed the data, revealing significant benefits of mnemonic strategies for short and long-term retention. The findings emphasized the importance of mnemonics in enhancing language retention. Educators are urged to integrate mnemonic techniques for improved retention. Future research could explore the long-term impact of mnemonics across subjects and student groups.